Mednarodna perspektiva Afriške unije na nemirni afriški celini - Majcen, Slavko (Vojaškošolski zbornik, 2024)
As Africa's central forum for promoting multilateral cooperation, peace, security and sustainable development, the African Union plays an important role in international relations. Established as the successor to the Organisation of African Unity, the African Union brings together all 55 sovereign African states and is an outstanding example of international cooperation. This paper analyses the structure of the AU and its policies, achievements and challenges, and critically evaluates its impact on building the global order and on regional integration. In addition, the paper explores, from a qualitative perspective, the African Union's contribution to maintaining international order, its engagement with global challenges, and its position-taking in international relations. Through this research approach, the African Union is recognized as a key actor which not only represents the interests of African countries on the world stage, but also actively participates in the shaping of international norms and policies, in advocacy for peace and security, and in the promotion of democracy, human rights, and sustainable development.
Keywords: African Union; Afriška unija; international order; Mednarodne organizacije; Mednarodni odnosi; mednarodni red; mir in varnost; peace and security; regional integration; Regionalizem (mednarodna skupnost); regionalna integracija; sustainable development; trajnostni razvoj; Vojaška politika